Reduced Willingness to Expend Effort for Reward in Obesity: Link to Adherence to a 3‐Month Weight Loss Intervention. Issue 10 (7th August 2017) - Mata, Fernanda; Treadway, Michael; Kwok, Alastair; Truby, Helen; Yücel, Murat; Stout, Julie C.; Verdejo‐Garcia, Antonio
Abstract : Objective: This study aimed to (1) compare the willingness to expend effort for rewards between young adults with healthy weight, overweight, and obesity; and (2) to examine how individual differences in the willingness to expend effort for rewards predict adherence to weight loss treatment. Methods: Seventy‐three participants completed the Effort Expenditure for Rewards Task (EEfRT). Of those 73 participants, 42 young adults with excess weight took part in a 3‐month weight loss treatment after completing the EEfRT. Generalized estimating equation models were used to compare the groups with healthy weight, overweight, and obesity in the EEfRT. Logistic regression models, including the proportion of hard‐task choices for each reward probability condition as predictors (12%, 50%, and 88%), were conducted to longitudinally predict adherence in the treatment. Results: Young adults with obesity were significantly less willing to expend effort for high‐magnitude rewards compared with participants with overweight ( P = 0.05). The willingness to expend effort for uncertain rewards (50% probability) was distinguished between completers and dropouts in the weight loss treatment (χ 2 = 5.04, P < 0.02). Conclusions: Young adults with obesity, compared with their counterparts with overweight, have diminished motivation to expend effort for obtaining high‐magnitude rewards. Less willingness to expend effort for the most uncertain rewards predicts poor adherence to weight loss treatment.